3D Analysis of maxillary incisor root inclinations in cases of unilateral maxillary canine impaction. (1st October 2021) - Light, Nathan; Chaushu, Stella; Major, Paul W; Flores-Mir, Carlos
Summary: Objectives: To evaluate the association between maxillary incisor root inclinations and unilateral canine impaction. Methods: A retrospective cross-sectional study of 59 pre-treatment CBCT scans (23 palatal impactions, 10 buccal impactions, and 26 comparison patients). Using Dolphin 3-D Imaging software (Chatsworth, CA), relative incisor angulations to a 3D palatal plane and the shortest distance between the canine crown and the root of the closest lateral incisor were calculated. A one-way analysis of variance was used to determine whether there were any differences between the three independent groups of impactions concerning the four continuous dependent variables incisor root inclination for each maxillary incisor. Results: Patients with unilaterally impacted maxillary canines demonstrate significant differences in the root inclination position on the ipsilateral (0.0001 > P = 0.002) but not contralateral side. While palatal impactions (PIC) are associated with buccally positioned roots of the ipsilateral lateral (−9.05 degrees) and central incisors (−7.91 degrees), buccal impactions (BIC) are only associated with palatally positioned roots of the ipsilateral lateral incisors (+10.40 degrees) alone. A more labial position of the lateral incisor root was correlated with a more proximally located, coronally positioned, and medially displaced adjacent PIC (0.013 > P < 0.026). Limitations: This is a retrospective cross-sectional convenience sample. Conclusions: Patients with impacted maxillary canines, whether PIC or BIC, do not show generalized retroclination or proclination of all four maxillary incisor roots. Instead, changes in incisor root inclination were only ipsilateral to the impacted canine. BIC is only associated with palatal displacement of the ipsilateral lateral incisor root, whereas PIC is associated with labial root displacement of both ipsilateral incisors.